T-cell and mast cell lines respond to B-cell stimulatory factor 1. - Mosmann, T R (1986)
The murine lymphokine B-cell stimulatory factor 1 (BSF-1) has been described previously in terms of its action on B lymphocytes. We now provide evidence that BSF-1 is also responsible for two additional biological activities. The first of these is the stimulation or maintenance of a state of activation in mouse T-cell lines. The second activity is the increase in the proliferative rate of certain mast cell lines costimulated with interleukin 3. The T-cell and mast cell activities are mediated by purified BSF-1 and copurify with BSF-1 from supernatants of certain T-cell lines. Each of these activities is inhibited by monoclonal anti-BSF-1 but not by monoclonal anti-interleukin 2 antibody. The antibody inhibition results also indicate that BSF-1 is the major or only source of these two activities in the activated T-cell supernatants that we have tested.